2021
DOI: 10.37275/bsm.v6i1.436
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Catheter-Related Infection in Patients Undergoing Hemodialysis Using Double Lumen Catheter at Dr. M. Djamil Hospital Padang

Abstract: Background. Chronic kidney disease (CKD) is a terminal disease requiring hemodialysis. Hemodialysis requires vascular access using a double lumen catheter (DLC). However, the use of DLC may increase complications mainly infection, either infection of exit site or bloodstream. This study is aimed to seek risk factors contributing to the incidence of central catheter-related infections in CKD patients with DLC undergoing HD at Dr. M. Djamil Hospital, Padang. Methods. This study is a prospective study on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This number is not much different from the results of a study by Wiradana et al, (Wiradana et al, 2021) in 2021 in Denpasar which reported that 41.2% of 102 patients undergoing hemodialysis had CDL infections. In a study by Iqbal et al, (Iqbal et al, 2022) in Padang in 2022, they reported a higher percentage of CDL infections, out of a total of 40 hemodialysis patients who underwent CDL installation, 27 patients (67.5%) had CDL infections. From this study, the results showed that there was no significant difference in sex and age between patients with and without CDL, so it can be concluded that the incidence of CDL infection in this study was not influenced by gender and age.…”
Section: Discussionmentioning
confidence: 98%
“…This number is not much different from the results of a study by Wiradana et al, (Wiradana et al, 2021) in 2021 in Denpasar which reported that 41.2% of 102 patients undergoing hemodialysis had CDL infections. In a study by Iqbal et al, (Iqbal et al, 2022) in Padang in 2022, they reported a higher percentage of CDL infections, out of a total of 40 hemodialysis patients who underwent CDL installation, 27 patients (67.5%) had CDL infections. From this study, the results showed that there was no significant difference in sex and age between patients with and without CDL, so it can be concluded that the incidence of CDL infection in this study was not influenced by gender and age.…”
Section: Discussionmentioning
confidence: 98%
“…14 Similarly, many African countries, Middle East and European studies reported a significant association between the incidence of CRBSIs and longer duration of CVC insertion. 10,15,16 In CKD patients, the possible reasons for the prolonged duration of CVC usage were due to the difficulty of performing an arteriovenous fistula (AVF). This is a common problem encountered in our center.…”
mentioning
confidence: 99%